Study of the Efficacy of Ischemia Reversal Program along with Restricted Diet in an Elderly Myocardial Ischemic Patient with a Known History of Hypertension - A Case Study (International Journal of Ayurveda and Pharma Research, 2023)
The biggest global cause of morbidity and mortality, according to the World Health Organization, are cardiovascular diseases (CVDs). Consequently, there is a need for new therapeutic modalities that will complement current CVD care tools. To evaluate the effectiveness of the Ischemia Reversal Program along with a restricted diet in an elderly myocardial ischemic patient with other comorbidities like Hypertension (HTN) and Hypokinesia.  60-year-old male had a myocardial ischemia episode in April 2020 and received standard allopathic medical care. The patient had a history of HTN. This patient opted for Ischemia Reversal Program (IRP) and dietary modification with Ayurveda-based medicines as an add-on complementary treatment to accelerate the healing process. The patient had elevated HTN (SBP/DBP: 123/74) according to the ambulatory blood pressure monitoring (ABMP) report which was reduced post-intervention (SBP/DBP: 109/66). The patient also showed hypokinetic anterior wall LV according to the 2D ECHO report while the post-intervention 2D ECHO report showed no regional wall motion abnormality. Findings of our study suggest that IRP which includes Ayurveda-based Panchakarma therapy along with dietary modifications can serve as treatment for patients with myocardial ischemia and other comorbidities like HTN, and hypokinesia.